From Contagium vivum fluidum to Riboviria: A Tobacco Mosaic Virus-Centric History of Virus Taxonomy - Zerbini, F. Murilo; Kitajima, Elliot W. (Biomolecules (Basel, Switzerland), 2022)
Viruses were discovered as agents of disease in the late 19th century, but it was not until the 1930s that the nature of these agents was elucidated. Nevertheless, as soon as viral diseases started to be recognized and cataloged, there were attempts to classify and name viruses. Although these early attempts failed to be adopted by the nascent virology community, they are evidence of the human compulsion to try to organize the natural world into well-defined categories. Different classification schemes were proposed during the 20th century, but again none were widely embraced by virologists. In 1966, with the creation of the International Committee on Nomenclature of Viruses (eventually renamed as the International Committee on Taxonomy of Viruses), a more organized effort led to an official taxonomy in which viruses were classified into families and genera. At present, a much better understanding of the evolutionary relationships among viruses has led to the establishment of a 15-rank taxonomy based primarily on these evolutionary relationships. This review of virus taxonomy will be centered on the tobacco mosaic virus (TMV), the agent of the disease studied by Dmitry Ivanovsky and the first virus to be recognized as such, which was often historically at the center of major advancements in virology during the 20th century.